Morphological and molecular characterization of Zygotylenchus gansuensis n. sp. (Nematoda: Pratylenchinae) from China - Wang, Honghong; Zhuo, Kan; Liao, Jinling (Zootaxa, 2014)
Zygotylenchus gansuensis n. sp. is described and illustrated from the rhizosphere of jujube (Zizyphus jujuba Mill.) based on morphology and molecular analyses. This new species is characterized by a low and flattened labial region with three annuli, stylet 14.1±0.5 (13.0–14.9) μm long, deirids absent, five lateral lines in the vulval region, pharyngeal glands overlapping ventrally or ventrolaterally, V = 56.4±1.6 (54.0–60.8), indistinct spermatheca, subcylindrical tail with smooth and rounded terminus, and males absent. Molecular analyses show that the species has unique partial SSU, LSU D2D3 and ITS rRNA sequences. Phylogenetic relationships of Z. gansuensis n. sp. with other nematodes in Pratylenchinae are analysed using SSU and LSU D2D3.